Effectiveness Analysis of Antidiabetic Property from Dragon Fruit Peel Methanol Extract in Alloxan-Induced Diabetic Rats - Sumartin, Sonia Apriani; Lister, I Nyoman Ehrich; Fachrial, Edy (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Diabetes is a health burden in various countries, one of these countries, is also Indonesia. Dragon fruit peel is an alternative diabetes therapy that has been widely studied. Therefore, this study aimed to investigate an antidiabetic effect of dragon fruit peel methanol extract on alloxan-induced diabetic male Wistar rats. This experimental study used twenty-five male Wistar rats induced by alloxan injection. After 48 hours, all rats were grouped into five different groups, including control (0.5% SCMC), standard (Metformin), Dragon Fruit Peel Methanol Extract-1 (500 mg/kg BW), 2 (750 mg/kg BW), and 3 (1,000 mg/kg BW). These treatments were given for two weeks. After that, all rats were dissected to obtain the pancreas. The results showed that dragon fruit peel methanol extract significantly decreased blood glucose levels after the 7th and 14th days (P value <0.05). In addition, pancreatic histology showed a decrease in the extract dose followed by a smaller size of the pancreatic Langerhans islet. The lowest dose of the extract showed a similar size of pancreatic Langerhans islet to the control group with an atrophic pancreatic Langerhans islet. Therefore, it can be concluded that dragon fruit peel extract can significantly decrease blood glucose levels and improve the structure of pancreatic Langerhans islet at higher doses.